Properties of Electrospun TiO2 Nanofibers - Bianca Caratão; Edgar Carneiro; Pedro Sá; Bernardo Almeida; Sandra Carvalho (Journal of Nanotechnology)
Titanium oxide filled polyvinylpyrrolidone (PVP) composite nanofibers have been prepared via a simple electrospinning technique. The combination of good TiO2 properties with its high surface area leads these nanofibers into having a vast applicability such as cosmetics, scaffolds for tissue engineering, catalytic devices, sensors, solar cells, and optoelectronic devices. The structural and chemical properties of the prepared samples have been studied. The presence of the TiO2 phase on the nanofibers was confirmed. An anatase to rutile transformation was observed at 600°C. Regarding the thermogravimetric and differential thermal analysis (TGA/DTA), the TIP decomposition and the PVP evaporation at 225°C were verified.